Social Undertones in William Robinson’s Crusade Against ‘Architects’ Gardens’: a ‘Costly Ugliness to Our Beautiful Home-landscapes’ (Robinson 1892, XIII) - Aurélien Wasilewski (Cahiers Victoriens et Edouardiens)
William Robinson (1838–1935) was an influential Irish gardener and journalist who came to be known as the main instigator of the English flower garden and cottage aesthetics that emerged in the latter part of the nineteenth century. His adamant rejection of artificial forms and colours in gardens came as a blow to the fashionable high-Victorian gardening style in which straight lines and geometrical patterns dominated in the form of topiary art, unvaried masses of colours, and flat land terracing. This paper purports to analyse, mainly through a corpus of Robinson’s newspaper articles, the socio-economic implications of his aesthetic choices. It seems that his rejection of artificiality and laudation of a more natural style of gardening was indeed a way of promoting the socio-professional figure of the gardener at the expense of the architect. By putting the plants’ needs and forms at the core of his definition of beauty, thus making horticultural knowledge the prerequisite to garden creation, he endeavoured to oust architects from the landscape profession. This natural aesthetics also theoretically entailed less care and fewer costs, which appealed to aspiring Victorian middle-classes who could acquire and share horticultural knowledge in the columns of Robinson’s popular gardening magazines. The community of gardeners gathered in those pages reflected a larger Weltanschauung in which the figure of the gardener embodied the possibility of harmonious coexistence and symbiosis between Victorians and Nature.